Enlargement of the knowledge of Cortinarius section Anomali (Agaricales, Basidiomycota): introducing three new species from China - Zhang, Qiu-Yue; Jin, Can; Zhou, Hong-Min; Ma, Zi-Yan; Zhang, Yi-Zhe; Liang, Jia-Qi; Si, Jing; Li, Hai-Jiao (Frontiers in Cellular and Infection Microbiology, 2023)
Cortinarius is a globally distributed agaricoid genus that has been well studied in Europe and America with over 1,000 described species. However, as part of an ongoing effort to investigate the diversity of Cortinarius section Anomali in China, the resource investigation and classification research are still limited, and the species diversity has not been clarified by far. During the re-examination of the Chinese Cortinarius specimens, C. cinnamomeolilacinus, C. subclackamasensis, and C. tropicus, belonging to the sect. Anomali, were described in China as new to science based on morphological examination and phylogenetic analysis. The three new species are described and illustrated in detail according to the Chinese materials. The phylogenetic analysis based on internal transcribed spacer sequences confirmed the placement of the three species in the Cortinarius sect. Anomali clade. Phylogenetically related and morphologically similar species to these three new species are discussed.